EDUCATIONAL QUALITY ISSUES IN THE PROCESS OF IMPLEMENTING DIGITAL TECHNOLOGIES IN THE MODERN EDUCATIONAL SYSTEM (Universal International Scientific Journal, 2026)
This article analyzes the current problems related to the quality of education in the process of introducing digital technologies into the modern education system. The impact of digitalization on the educational process, its pedagogical and psychological aspects, infrastructural shortcomings and ways to eliminate them are covered on a scientific and theoretical basis. Also, issues of increasing the efficiency of education through innovative approaches are revealed.
Keywords: : digital education, innovative technologies, quality of education, distance learning, pedagogical skills, digital competence, media literacy, educational effectiveness.